Hettangian and Sinemurian (Lower Jurassic) biostratigraphy of Argentina - Riccardi, Alberto Carlos (1991)
On the northern bank of the Rio Atuel, Mendeza province, Argentina, the marine fossilfferous Mesozoic is now known to begin with Hettangian-lower Sinemurian strata. Traditionally, the marine Jurassic sequence in the area was believed to start with upper Sinemurian levels. Representatives of the genera Psiloceras Hyatt, Caloceras Hyatt, Alsatites Haug, Waehneroceras Hyatt, Schlotheimia Bayle, Sulciferites Spath, Badouxia Guex and Taylor, Vermiceras Hyatt, Coroniceras Hyatt, Agassiceras Hyatt, Euagassiceras Spath, and Arnioceras Hyatt thus indicate the presence of beds equivalent to the Planorbis, Liasieus, Angulata, Bucklandi, Semicostatum, and Turneri zones of the standard international chronostratigraphic scale. Hence, in Argentina, the marine Hettangian, Sinemurian, and lowermost Pliensbachian have been proved only in the neighborhood of the Rio Atuel region, where marine Triassic could also be represented. Elsewhere in Argentina, the oldest Jurassic ammonite-bearing levels usually belong to the upper lower or the upper Pliensbachian. Regionally, these findings imply a substantial modification to previous paleogeographic reconstructions for the Early Jurassic of South America.